Mind Invasion: Situated Affectivity and the Corporate Life Hack - Slaby, Jan (Frontiers in Psychology, 2016)
In view of the philosophical problems that vex the debate on situated affectivity, it can seem wise to focus on simple cases. Accordingly, theorists often single out scenarios in which an individual employs a device in order to enhance their emotional experience, or to achieve new kinds of experience altogether, such as playing an instrument, going to the movies or sporting a fancy handbag. I argue that this narrow focus on cases that fit a ‘user/resource model’ tends to channel attention away from more complex and also more problematic instances of situated affectivity. Among these are scenarios in which a social domain draws individuals into certain modes of affective interaction, often by way of attunement and habituation to affective styles and interaction patterns that are normative in the domain in question. This can lead to a phenomenon that is not so much ‘mind extension’ than ‘mind invasion’: affectivity is dynamically framed and modulated from without, often contrary to the prior orientations of the individuals in question. As an example, I discuss affective patterns prevalent in today’s corporate workplace. I claim that workplace affect sometimes contributes to what is effectively a ‘hack’ of employees’ subjectivity.